1963
DOI: 10.1119/1.1969660
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Scientific Revolutions

Abstract: Articles you may be interested inEinstein and Lorentz: The structure of a scientific revolution Am.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
6

Year Published

1969
1969
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 416 publications
(40 citation statements)
references
References 0 publications
0
34
0
6
Order By: Relevance
“…When a solution of the crystalline ammonium salt of 3-deoxy D-mannO-OCtUlOSOniC acid in 0.1 N sulphuric acid was treated with periodate at 0" and the kinetics of periodate reduction and j3-formyl-pyruvate formation were followed (Fig.l), it was found that 3 molar equivalents of periodate were reduced within 6-7 h and that, at the same time, the amount of /$formy1 pyruvic acid liberated attained its maximum. The molar extinction coefficient reached a t this point the value of 95 x lo3 and remained virtually constant for the next 10 h. A slow, apparently linear decrease was then observed during 50 h. The molar extinction coefficient, 95-98 x lo3, was about 1501, higher than the one ( 8 1~1 0~) given [24] for the crystalline dye. (Kuhn and Lutz [24] established the extinction coefficient for an aqueous solution a t (presumably) pH 7, while in our conditions the extinction coefficient is measured in acid solution ; we found that the extinction coefficient of the dye formed from b-formyl-pyruvate and thiobarbiturate varies with the pH ; the same observation was made for the dye formed from malonaldehyde and thiobarbiturate [25].)…”
Section: Periodate Oxidation and Thiobccrbiturate Test Of 3-deoxy D-mmentioning
confidence: 73%
See 4 more Smart Citations
“…When a solution of the crystalline ammonium salt of 3-deoxy D-mannO-OCtUlOSOniC acid in 0.1 N sulphuric acid was treated with periodate at 0" and the kinetics of periodate reduction and j3-formyl-pyruvate formation were followed (Fig.l), it was found that 3 molar equivalents of periodate were reduced within 6-7 h and that, at the same time, the amount of /$formy1 pyruvic acid liberated attained its maximum. The molar extinction coefficient reached a t this point the value of 95 x lo3 and remained virtually constant for the next 10 h. A slow, apparently linear decrease was then observed during 50 h. The molar extinction coefficient, 95-98 x lo3, was about 1501, higher than the one ( 8 1~1 0~) given [24] for the crystalline dye. (Kuhn and Lutz [24] established the extinction coefficient for an aqueous solution a t (presumably) pH 7, while in our conditions the extinction coefficient is measured in acid solution ; we found that the extinction coefficient of the dye formed from b-formyl-pyruvate and thiobarbiturate varies with the pH ; the same observation was made for the dye formed from malonaldehyde and thiobarbiturate [25].)…”
Section: Periodate Oxidation and Thiobccrbiturate Test Of 3-deoxy D-mmentioning
confidence: 73%
“…Separation of the keto-acid The most extensively used method for the estimation of 3-deoxy aldulosonic acids is based on the observation [gal that, when treated with periodate, these acids give rise to j3-formyl-pyruvic acid (VI), which, upon condensation with thiobarbituric acid, forms a red dye. The structure of the dye formed, as well as its molar extinction coefficient in aqueous and in cyclohexanone solutions, have been established by Kuhn and Lutz [24] ; it has an absorption maximum a t 549 nm. This dye can be differentiated from a similar one ( A, , , 532), which is formed from malonaldehyde and thiobarbituric acid in essentially the same conditions, by its instability towards base [3, 261 and its slightly different absorption maximum.…”
Section: Periodate Oxidation and Thiobccrbiturate Test Of 3-deoxy D-mmentioning
confidence: 98%
See 3 more Smart Citations